Between past and future: Current challenges and significance of the geohistorical study of Society and its relationship with Nature at various geographic- and time-scales - Samper Kutschbach, Mario (2025)
An interpretive essay on collaborative and institutional approaches to the study of significant changes in human societies and in their relations with Nature, at various geographic- and time-scales, in connection with historical research and training in History and Social Studies since the 1970s at the History Department of Universidad Nacional and in its graduate program in Applied History. Based on the author´s direct experience, this overview focuses primarily on a thirty-year period after the mid-70s, with certain references to interactions with related academic processes at Universidad de Costa Rica and collaboration with the Central American Historical Research Center. This essay also explores certain international relations and influences, and addresses -more briefly- recent academic work on specific topics, with an emphasis on historical-geographic aspects.